Pengaruh Budaya Organisasi Terhadap Perilaku Kewargaan Organisasi Karyawan - Nur Annisa; Tintin Suhaeni (Jurnal Riset Bisnis dan Investasi, 2016)
Organizational culture is one of the important things that must be considered by a company because it causes the appearance of organizational citizenship behavior in the employee. Positive organizational culture cause the employees felt like to do more work than what was required in the job description. This research aims to figure out the organizational culture, citizenship behavior, and how much influence from organizational culture into citizenship behavior employees in PT X. The method research is using quantitative research method. The data analysis method was used that classic assumption test, descriptive statistical analysis, simple correlation analysis, simple linear regression analysis, and hypothesis testing. The sample in this research of 120 respondents with the total population of 239 employees. Collecting data use questionnaire with the Likert scale and interview. The results showed the organization's culture is in the category both in terms of innovation and risk-taking, attention to detail, results-orientation, people orientation, team orientation, aggressiveness, and stability. Then the organizational citizenship behavior was used in this study is the dimension of organizational citizenship behavior of employees also are in good category seen from the behavior altruism, conscientiousness, Sportsmanship, courtesy, and civic virtue. The conclusion from this research that there is an influence of organizational culture on organizational citizenship behavior amounted to 79.3%.